PATHOGENESIS OF MICROBIAL KERATITIS (LITERATURE REVIEW) (World Bulletin of Public Health, 2025)
Microbial keratitis is a sight-threatening eye infection caused by bacteria, fungi, and protists. Defects and damage to the epithelium are key predisposing factors that make the eye susceptible to corneal pathogens. Among bacterial pathogens, the most common causative agents of keratitis are Staphylococcus aureus, Pseudomonas aeruginosa, Streptococcus pneumoniae and Serratia species. Fungal causative agents of corneal infections include both filamentous and yeast fungi, including Fusarium, Aspergillus, Phaeohyphomycetes, Curvularia, Paecilomyces, Scedosporium, and Candida, and among protists, Acanthamoeba spp. are responsible for ocular disease. Clinical signs include redness, pain, lacrimation, blurred vision, and inflammation, but symptoms vary depending on the causative agent.